Numerical Analyses of Earthquake Induced Liquefaction and Deformation Behaviour of an Upstream Tailings Dam - Muhammad Auchar Zardari; Hans Mattsson; Sven Knutsson; Muhammad Shehzad Khalid; Maria V. S. Ask; Björn Lund (Advances in Materials Science and Engineering)
Much of the seismic activity of northern Sweden consists of micro-earthquakes occurring near postglacial faults. However, larger magnitude earthquakes do occur in Sweden, and earthquake statistics indicate that a magnitude 5 event is likely to occur once every century. This paper presents dynamic analyses of the effects of larger earthquakes on an upstream tailings dam at the Aitik copper mine in northern Sweden. The analyses were performed to evaluate the potential for liquefaction and to assess stability of the dam under two specific earthquakes: a commonly occurring magnitude 3.6 event and a more extreme earthquake of magnitude 5.8. The dynamic analyses were carried out with the finite element program PLAXIS using a recently implemented constitutive model called UBCSAND. The results indicate that the magnitude 5.8 earthquake would likely induce liquefaction in a limited zone located below the ground surface near the embankment dikes. It is interpreted that stability of the dam may not be affected due to the limited extent of the liquefied zone. Both types of earthquakes are predicted to induce tolerable magnitudes of displacements. The results of the postseismic slope stability analysis, performed for a state after a seismic event, suggest that the dam is stable during both the earthquakes.